"Semaumaq": the efficacy and journey of facilitating family dyadic interaction in a Paiwan indigenous community in Taiwan. Issue 3 (3rd July 2022) - Pan, Cheng-Chen; Wang, Hui-Ting; Pan, Yu-Fong; Chao, Chia-Yi; Pan, Cheng-Hsien
ABSTRACT: Semaumaq means "return home" in the Paiwanese language. This article explored and described the efficacy and journey of a research team in facilitating culturally appropriate family dyadic interactions in a Paiwanese community in Taiwan using a shared book-reading program. This program was implemented in a rural elementary-school-affiliated preschool in a Paiwanese village in southern Taiwan. Eight families participated. A naturalistic inquiry method using a feedback form, strategy checklist, observations, brief interviews, and video recording was used to collect the data. "Enjoyment and improving family relationships" was identified as the core theme of the parent-child interaction experiences elicited during the program. The results of this naturalistic inquiry support the efficacy and acceptability of using parent-child shared book-reading programs in indigenous communities. The elements of the program that may have contributed to its success are described. Future research may adopt an experimental design to further validate and clarify results.